EP742 Cancer genomic and personalized medicine for gynecologic tumors in our hospital. (1st November 2019) - Oshima, N; Takahashi, K; Nakamura, R; Yoshino, Y; Wakana, K; Ikeda, S; Miyasaka, N
Abstract : Introduction/Background: Cancer genomic and personalized medicine has widely used globally and Department of Cancer Genomics was newly opened in our hospital in Tokyo, Japan. The aim of this study was to review the patients who were referred to the department for gynecologic cancers. Methodology: Medical records of the patients who underwent cancer genome analysis for the gynecologic tumors between September 2017 and December 2018 were retrospectively reviewed. Results: Ten patients were found including ovarian cancer (n=4), cervical cancer (n=3), peritoneal cancer (n=1), uterine sarcoma (n=1) and ovarian borderline tumor (n=1). All of the cases had completed standard therapy and showed treatment-resistant recurrences. Cancer genome analyses were performed by extracting DNA from the formalin-fixed and paraffin-embedded tumor tissue in 9 cases and from blood sample in one case. Among them, candidate medicines were found in 2 cases. In the other 8 cases, medicines for the targeted gene was under development and clinically unavailable. Conclusion: This time, treatment was only performed in 2 out of 10 cases (20%). In many cases, the drug could not be reached even after the examination. It would be required to establish medical systems to access to the therapeutic agent without difficulty in the future. Disclosure: Nothing to disclose.